Addressing Disease-Related Stigma During Infectious Disease Outbreaks. (December 2019) - Fischer, Leah S.; Mansergh, Gordon; Lynch, Jonathan; Santibanez, Scott
ABSTRACT: Outbreaks of emerging infectious disease are a constant threat. In the last 10 years, there have been outbreaks of 2009 influenza A (H1N1), Ebola virus disease, and Zika virus. Stigma associated with infectious disease can be a barrier to adopting healthy behaviors, leading to more severe health problems, ongoing disease transmission, and difficulty controlling infectious disease outbreaks. Much has been learned about infectious disease and stigma in the context of nearly 4 decades of the human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome pandemic. In this paper, we define stigma, discuss its relevance to infectious disease outbreaks, including how individuals and communities can be affected. Adapting lessons learned from the rich literature on HIV-related stigma, we propose a strategy for reducing stigma during infectious disease outbreaks such as Ebola virus disease and Zika virus. The implementation of brief, practical strategies such as the ones proposed here might help reduce stigma and facilitate more effective control of emerging infectious diseases.